Calcium bioavailability from the kale (Brassica-oleracea) consumed as a complement of a basal rice and bean diet - Bicudo, M. H.; Maffia, L. M.; Rosa, G. P.; Lopes, C. G. (Inst Tecnologia Parana, 1990)
The bioavailability of calcium from the kale (Brassica oleracea var. acephala) consumed as a complement of a basal rice and bean diet was studied. Three groups of diets, two controls and one experimental were fed to Wistar female rats. The protein source of the first control was casein and of the second, a mixture of bean and rice. To both groups, graded levels of CaCO3 were added. The experimental diet was similar to the second control, except that CaCO3 was substituted for kale supplying the same amount of calcio. At 35 days of experimental period, they were killed and the calcium and phosphorus were determined in the right femur. The results indicated that the calcium from the kale is better utilized than that of the CaCO3. There was no significant difference in the concentration of calcium in the soft tissues studied among three dietary groups. Considering the high concentration and availability of calcium from the kale its consumption as a complement of the basal rice and bean diet may be recommended as a cheap and good source of this mineral.